Neutrophil gelatinase–associated lipocalin as an immunomodulator in endocrine hypertension - Araos, Patricio; Amador, Cristián A. (Frontiers in Endocrinology, 2022)
In recent studies, primary aldosteronism (PA) was reported as the most common etiology in approximately 10% of patients with secondary hypertension of endocrine origin. In PA, excess aldosterone production can lead to deleterious effects at cardiovascular (CV) and renal levels by activating the mineralocorticoid receptor, which involves an increase in pro-inflammatory and pro-fibrotic mediators. Among these mediators, neutrophil gelatinase-associated lipocalin (NGAL), a secretion glycoprotein belonging to the lipocalin superfamily, has been closely linked to CV and renal damage in several pathological conditions. Because NGAL can be detected in biofluids, such as plasma and urine, not only has it been proposed as a damage biomarker for target tissues, but it also has been studied in hypertension and associated with PA. NGAL has varied origins, from epithelial cells to immune cells, being carried on extracellular vesicles, and modulated by microRNAs, which would support its use as a biomarker for endocrine hypertension due to PA. In the last decade, studies have shown that NGAL is required to develop aldosterone-induced hypertension and is associated with end-organ damage. In addition, some mechanisms were proposed to be dependent on the activation of immune cells, such as dendritic cells and macrophages, where the release of specific cytokines (IL-23) or chemokines (CCL-5) induced by aldosterone would depend on NGAL. Subsequently, this activates the T helper (Th) lymphocytes, such as Th17 and Th2, resulting in CV and renal fibrosis because of high aldosterone levels. Although the immune system has been strongly associated with essential hypertension, its participation in endocrine hypertension has not been fully elucidated. This review discusses the link between NGAL and endocrine hypertension, particularly in PA, and their possible regulators and mechanisms, while focusing on its role as an immunomodulator.